Analisis Kualitas Butir Soal Ujian Akhir Semester Ganjil Tahun Pelajaran 2020/2021 Mata Pelajaran Biologi Kelas X SMA Negeri 1 Teluk Sebong - Suci Mitra Prawiki; Helendra Helendra (Universitas Sultan Ageng Tirtayasa, 2022)
Evaluation is an activity carried out to measure the process of student learning outcomes and determine the achievement of learning objectives. Good quality questions are needed to provide accurate information on the abilities of students. The teacher at SMAN 1 Teluk Sebong did not analyze the items due to limited free time and the teacher's lack of understanding in analyzing the questions. This research aims to determine of quality the question final exam odd semester 2020/2021 biology class x sma negeri 1 teluk sebong. This research is a type of descriptive research with qualitative and quantitative descriptive data analysis techniques. Data collection techniques with observation, interviews and documentation. Qualitative descriptive analysis used item review sheets to determine the quality of the questions in terms of material, construction, and language. Quantitative descriptive analysis using Anates version 4.0.9 program to determine item validity, item reliability, discriminatory power, level of difficulty, and effectiveness of distractors. The results showed that in terms of (1) material aspects 99% appropriate categorized as very good, (2) construction aspects 95% appropriate categorized as very good, (3) language aspects 93% appropriate categorized as very good, (4) item validity 43% items are valid and 57% items are invalid, (5) questions reliability with a reliability index of 0.78 is categorized as very high, (6) discriminatory power of 27% items is good, 43% of items is sufficient, and 30% of items are bad, (7) difficulty level is 20% easy items, 57% moderate items, and 23% difficult items, (8) distractor effectiveness 41% very good option, 31% good option, 20% less option, 5% bad option, and 3% option is very bad. Conclusion analysis of quality the question final exam odd semester 2020/2021 biology class x sma negeri 1 teluk sebong in terms of material, construction, and language aspects is very good, has sufficient item validity, high reliability, sufficient discriminatory power, medium difficulty, and good distractor effectiveness.